Aerobic and anaerobic determinants of repeated sprint ability in team sports athletes - Gharbi, Z.; Dardouri, W.; Haj-Sassi, R.; Chamari, K.; Souiss, N. (Biology of Sport, 2015)
The aim of this study was to examine in team sports athletes the relationship between repeated sprint ability (RSA) indices and both aerobic and anaerobic fitness components. Sixteen team-sport players were included (age, 23.4 ± 2.3 years; weight, 71.2 ± 8.3 kg; height, 178 ± 7 cm; body mass index, 22.4 ± 2 kg · m-2; estimated VO2max, 54.16 ± 3.5 mL · kg-1 · min-1). Subjects were licensed in various team sports: soccer (n = 8), basketball (n = 5), and handball (n = 3). They performed 4 tests: the 20 m multi-stage shuttle run test (MSRT), the 30-s Wingate test (WingT), the Maximal Anaerobic Shuttle Running Test (MASRT), and the RSA test